sigma-Holes - Clark, Timothy (Wiley Interdisciplinary Reviews: Computational Molecular Science, 2013)
sigma-Holes are regions of positive molecular electrostatic potential collinear with and opposite to covalent bonds to atoms of Groups IV-VII. They are responsible for many noncovalent bonding interactions, such as halogen bonding. sigma-Holes make 'negatively charged' atoms act as if they were 'positively charged'. The existence of sigma-hole bonding emphasizes what has been called 'the fallacy of net atomic charges', which means that many covalently bonded atoms cannot be represented adequately by a single charge because they look negative from some directions and positive from others. Hydrogen bonding can also be regarded as a special case of sigma-hole bonding, although in this case the origin of the sigma-hole is rationalized differently than in the heavier elements. Phenomena such as the directionality of hydrogen bonds and 'blue-shifted' hydrogen bonds can be explained very simply using the sigma-hole concept. (C) 2012 John Wiley & Sons, Ltd. How to cite this article: WIREs Comput Mol Sci 2013, 3:13-20 doi: 10.1002/wcms.1113